La política petrolera en el gobierno de la revolución ciudadana: El caso del Campo Sacha - García-Osorio, Nelson (Editorial Grupo AEA, 2022)
In the first part, a summary of oil management from 1972 to the present is made, as well as a description of the oil policy applied by the governments, from the administration of Dr. Oswaldo Hurtado to the administration of Mr. Guillermo Lasso. The second part analyzes the legal environment in the context of natural resources, especially oil, within the framework of the Hydrocarbons Law and the Constitution of the Republic of Ecuador. And in the third, we analyze the production in the Sacha Field, awarded to ORNCEM through the specific services contract and according to its two amendment contracts. It concludes with some considerations that should be taken into account and that call for reflection when contracts are proposed and executed whose benefit is not the best for the country. On the other hand, forests are great "cleaners" of carbon dioxide; when they are destroyed, their absorption potential is annulled and, therefore, they contribute to global warming by increasing greenhouse gases, which is why deforestation must be counteracted.